2021
DOI: 10.1021/acsanm.1c01425
|View full text |Cite
|
Sign up to set email alerts
|

Amino-Functionalized Ti3C2 MXene Quantum Dots as Photoluminescent Sensors for Diagnosing Histidine in Human Serum

Abstract: As an emerging zero-dimensional nanomaterial, MXene quantum dots (MQDs) have aroused the interest of researchers because of their unique physical and chemical characteristics. Here, a straightforward hydrothermal strategy was used to successfully produce the amino-functionalized Ti 3 C 2 MQDs. The functionalized Ti 3 C 2 MQDs exhibited bright blue fluorescence (FL), which was derived from its size effect and surface defects. In addition, Ni 2+ can bind to the amino groups on the surface of Ti 3 C 2 MQDs. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 60 publications
0
32
0
Order By: Relevance
“…MXene-based QDs illustrated great potentials for enhancing the specificity and sensitivity of sensors deployed for detecting proteins, genes, and viral particles [ 11 ]. For instance, to identify the histidine in human serum, amino-functionalized Ti 3 C 2 MXene QDs with bright blue fluorescence and high bio-affinity were prepared [ 72 ]. Furthermore, biocompatible aerogels with good stability have been constructed from MXene QDs and watermelon peel by immersing freeze-dried fresh watermelon peel into the QD dispersion; these nanosystems demonstrated suitable functionality in biosensing appliances [ 73 ].…”
Section: Biomedical Advancementsmentioning
confidence: 99%
“…MXene-based QDs illustrated great potentials for enhancing the specificity and sensitivity of sensors deployed for detecting proteins, genes, and viral particles [ 11 ]. For instance, to identify the histidine in human serum, amino-functionalized Ti 3 C 2 MXene QDs with bright blue fluorescence and high bio-affinity were prepared [ 72 ]. Furthermore, biocompatible aerogels with good stability have been constructed from MXene QDs and watermelon peel by immersing freeze-dried fresh watermelon peel into the QD dispersion; these nanosystems demonstrated suitable functionality in biosensing appliances [ 73 ].…”
Section: Biomedical Advancementsmentioning
confidence: 99%
“…MQDs have been applied to biomedical [ 129 , 130 ], optical device [ 131 133 ], energy storage [ 134 138 ], and sensor fields [ 112 , 139 , 140 ] due to that they possess the advantages of non-toxicity, metal conductivity, excellent chemical stability and low cost. Currently, the research of pure MQDs cannot meet the development needs of practical application.…”
Section: Preparation Of Mqdsmentioning
confidence: 99%
“…Constructing surface defect is an effective strategy. Furthermore, studies have shown that the passivation of surface defects induced by amino groups facilitates to improve the PL properties of MQDs, resulting in bright blue fluorescence and enhanced fluorescence lifetime [ 140 ]. The doping includes both non-metallic elements such as N, P, and S, and transition metal elements such as Ni, Co, and Cu.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…The ternary MAX phase can be easily converted into two-dimensional (2D) layered MXene sheets using a simple wet chemical etching process [10] and can be further reduced to zero-dimensional MXene quantum dots (MQDs) [26]. Similar to 2D materials such as graphene [27] and transition metal dichalcogenide (TMD)-based quantum dots [28][29][30], MQDs have become a center of interest for many researchers because of their excellent properties, such as good light emission [31,32], selective metal ion sensing [33][34][35][36], nontoxicity [26,37,38], biocompatibility [26], hydrophilicity [35], and functionalization [39,40]. Owing to their interesting optical properties, they can be used as crucial materials in optical sensors [41,42], bio-imaging [34], optical modulator [43] etc.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their interesting optical properties, they can be used as crucial materials in optical sensors [41,42], bio-imaging [34], optical modulator [43] etc. Comparatively, carbide MQDs [44,45] derived from the MAX phase containing a carbide group such as V 2 AlC [46], Nb 2 AlC [33], and Ti 3 AlC 2 [39] have been studied more than nitride MQDs [10,26]; thus, the exploration and broad study of the properties and applications of nitride based MQDs are necessary.…”
Section: Introductionmentioning
confidence: 99%